Contemporary Issues in Collection Management - Cameron, Kelsey; Chiovelli, Chelsea; Deschamps, Danielle; Grande-Sherbert, Marty; Hakimizadeh, Sadaf; Ip, Andrew; Komarnytska, Olesya; Nowakowsky, Amy; Pei, Winston; Pope, Nicole; Pouliot, Reis; Ramsey, Melissa; et al. (Open textbook library., 2023)
This edited, openly licensed, textbook examines several different issues in collection management. Topics covered include physical vs. digital collections; the impact of BookTok on collections; challenges to 2SLGBTQ+ collections ; ebook licensing; ebook pricing; accessible collections for users with physical disabilities; accessible collections for users with invisible disabilities; "just in time"/demand-driven acquisitions; climate change and collections and research data collections.